Optoelectronic time-division multiplexing for multicomponent laser doppler anemometry - Lockey, R. A. (Cranfield University, 1996)
This thesis describes the investigation of time-division multiplexing for use in mUlticomponent laser Doppler anemometry (LDA). To make two- or three- dimensional velocity measurements of a flow, two or three separate velocity measurements in different, non-collinear or non-coplanar directions respectively must be taken from which the flow vector can be calculated. It is necessary to separate each velocity channel. Conventionally, the separation is carried out by optical techniques, such as separating the signal from each channel by wavelength or polarisation, with one detector per channel. In time division multiplexing, each channel is switched On and off in turn. A single detector records a stream of interleaved pulses, and each channel is extracted by taking every other or every third pulse. The envelope of the amplitudes of the pulses varies at the Doppler frequency. A novel system has been demonstrated which uses a single laser diode source and a single detector. The distribution of the pulses to each channel and the delay between each channel is carried out using a optical fibre network with fibre delay lines, with a consequent reduction in 'electronic complexity. The characteristics of the optoelectronic components used in the system are tested, and two signal processing schemes are investigated. A two-dimensional Doppler difference fibre-linked probe was constructed to demonstrate the technique. Hybrid instruments using two Doppler difference channels and a reference beam channel to measure orthogonal velocity components offer the possibility of avoiding the errors introduced by non-orthogonal systems. A pulsed-diode reference beam anemometer based on optical fibres and suitable for inclusion in a time-division multiplexed hybrid instrument was tested.